Analisis Minat Konsumsi Masyarakat Dalam Meningkatkan Laba Penjualan Oleh-Oleh Khas Pasaman Barat Setelah Covid-19: (Studi Kasus Rumah Produksi UMKM Emping Jagung Mentega Kabupaten Pasaman Barat) - Laila Fitri; Sri Sudiarti; Nur Fadhilah Ahmad Hasibuan (Journal of Islamic Economics and Finance, 2023)
This research aims to find out whether people's consumption interest can increase profits from sales of West Pasaman specialty souvenirs, namely UMKM Corn Butter Chips after Covid-19. This research uses a qualitative method with a descriptive approach. The data collection technique in this research uses interview techniques, direct observation and literature study. The data analysis techniques in this research are data collection, data reduction, data presentation, and drawing conclusions. The research subject in this research is the owner of the UMKM Corn Butter Emping production house, namely Mr. Ade Media Saputra in Pinaga Village, Aua Kuniang, Pasaman District, West Pasaman Regency. Apart from that, several communities are responsible for providing the information needed by researchers. The sales data used in this research is data for 2018, 2019, 2020, 2021, and 2022 to see any changes in sales of UMKM Corn Butter Chips caused by Covid-19. The results of this research show that the sales profit of UMKM Corn Butter Chips after Covid-19 increased quite significantly compared to when Covid-19 occurred, reaching a percentage of 1.74% and a difference of Rp. 90,000,000, however, this sales profit has not yet reached the profit before Covid-19 occurred. Then, public interest in consumption can increase profits from sales of Butter Corn Emping souvenirs after Covid-19, as evidenced by the increase in public demand for Butter Corn Emping souvenirs with a percentage of 1.74% and a difference in demand of 1,800 kg.